Improvement of procedure of development and commercialization of new technologies - Dung, Bui Tien (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
The paper is focused on description of the procedure of development and commercialization of technologies in form of a theoretical model. This study offers certain helps to researchers and administrators for a better understanding of phases in the process of development and commercialization of new technologies. The procedure is proposed in a synthetized approach including the whole process from scientific ideas up to commercialization of new technologies. The process of development of new technologies includes many phases where the one of R&D holds the dominating roles. This study focuses main attentions on present possibilities to forecast successful outcomes of R&D projects from point of vision of development and commercialization. In addition, the proposed procedure of development and commercialization of new technologies gathers potentials to be used as a model for implementation of R&D projects in science and technology (S&T) organizations in Vietnam. Code: 15031001